The spiritual dimension and curriculum change - Buchanan, Michael T. (International journal of children's spirituality, 2009)
The impetus for curriculum change should ultimately be to improve student learning. Implementing change can be very stressful and diminish a teachers’ sense of well‐being and thereby minimise the chances of successful or effective change. Drawing on a recent study that investigated how faculty leaders managed curriculum change in religious education this paper reports on one key finding which suggested that attention to the spiritual dimension can help teachers to overcome feelings of anxiety and stress and lead to effective change management. In particular this paper identifies some characteristics of connectedness as expressions of the spiritual dimension within an educational context. This paper will situate the findings and provide a brief background to the study and the role of faculty leaders in managing curriculum change. It will then proceed to give an account of the spiritual dimension and how it may be fostered through experiences of connectedness within the educational setting. An overview of some characteristics of connectedness used by the faculty leaders are then outlined and conclusions drawn.